The relationship between free limb motions and performance in the triple jump - Yu, B.; Andrews, J. G. (Journal of Applied Biomechanics, 1998)
The purpose of this study was to investigate relationships between free limb motions and triple jump performance. The subjects were 13 elite male triple jumpers. Three-dimensional videographic data were collected using a direct linear transformation technique with panning cameras. Changes in the velocity of the whole body center of gravity (G), changes in the whole body angular momentum about G, changes in the velocity of G due to free limb motions, and changes in the whole body angular momentum about G due to free limb motions were determined for each of the three support phases. Free limb motions were associated with decreases in the forward horizontal velocity of G and increases in the vertical velocity of G and significantly influenced changes of the corresponding velocity components of G when the changes were large. The free limb motions also created some angular momentum components about G during each support phase but did not significantly influence the changes of the corresponding angular momentum components of the whole body. Neither the changes in the three velocity components of G nor the changes in the three angular momentum components of the whole body about G due to free limb motions were significantly related to the actual distance of the triple jump.